Odpowiedzi

Najlepsza Odpowiedź!
2009-11-27T17:01:04+01:00
A) ctgα + sinα/(1+cosα) = 1/sinα
ctgα + sinα/(1+cosα) = (cosα/sinα) + (sinα/1+cosα) = [(cosα*(1+cosα))/sinα(1+cosα)] + [(sin²α/sinα(1+cosα)] = (cosα + cos²α + sin²α)/sinα(1+cosα) = (cosα + 1)/sinα(1+cosα) = 1/sinα , co należało pokazać

b) cosα/(sinα-1) + tgα = - 1/cosα
cosα/(sinα-1) + (sinα/cosα) = cos²α/cosα(sinα-1) + [sinα*(sinα-1) /cosα(sinα-1)] = (cos²α + sin²α - sinα)/cosα(sinα-1) = (1 - sinα) /cosα(sinα-1) = - (sinα-1)/cosα(sinα-1) = -1/cosα , co należało pokazać

c) 1 - 2sin²α * cos²α = sin⁴α + cos⁴α
sin⁴α + cos⁴α = (sin⁴α + 2sin²α * cos²α + cos⁴α) - 2sin²α * cos²α =
(sin²α + cos²α)² - 2sin²α * cos²α = 1² - 2sin²α * cos²α = 1 - 2sin²α * cos²α , co należało pokazać
1 5 1